Accumulation of lipid peroxidation-derived DNA lesions: Potential lead markers for chemoprevention of inflammation-driven malignancies - Bartsch, Helmut; Nair, Jagadeesan (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2005)
Chronic inflammatory processes produce an excess of ROS and DNA-reactive aldehydes from lipid peroxidation (LPO), such as trans-4-hydroxy-2-nonenal (HNE) and malondialdehyde (MDA), which can modify cellular macromolecules and drive to malignancy. Etheno-modified DNA bases are generated inter alia by reaction of DNA with the major LPO product, HNE. We are investigating steady-state levels of etheno-DNA adducts in organs with diseases related to persistent inflammatory processes that can lead to malignancies. We have developed ultrasensitive and specific methods for the detection of etheno-DNA base adducts in human tissues and in urine. Etheno-DNA adduct levels were found to be significantly elevated in the affected organs of subjects with chronic pancreatitis, ulcerative colitis and Crohn's disease. When patients with alcohol abuse-related hepatitis, fatty liver, fibrosis and cirrhosis were compared with asymptomatic livers, excess hepatic DNA damage was seen in the three latter patient groups. Etheno-deoxyadenosine excreted in urine was measured in HBV-infected patients diagnosed with chronic hepatitis, cirrhosis and hepatocellular carcinoma. As compared to controls, these patients had up to 90-fold increased urinary levels. Impaired or imbalanced DNA-repair pathways may influence the steady-state levels of etheno-DNA adducts in inflamed tissues. In conclusion, etheno-DNA adducts may serve as potential lead markers for assessing progression of inflammatory cancer-prone diseases. If so, the efficacy of human chemopreventive interventions for malignant disease prevention could be verified.
Gesehen am 27.11.2020